Effect of ammoniacal thiosulfate solution composition on the gold dissolution rate: An electrochemical study (2024)
ABSTRACT: The electrochemical behavior of ammoniacal thiosulfate solutions (S2O3 2-- NH3-Cu2+ -EDTA) has been studied for varying electrolyte compositions in the gold electro-dissolution. A gold rotating disk electrode (RDE) was employed to measure anodic and cathodic polarization curves in alkaline thiosulfate solutions. Potentiodynamic polarization showed how thiosulfate, ammonia, and copper concentration influence the cathodic and anodic behavior of the electrolyte. Likewise, the influence of oxygen on the electrochemical behavior system was evi denced from the analysis of polarization curves, and using Koutecky – Levich equation (slope of 59.60 mV/ decade), it was possible to determine the peroxide pathway for oxygen reduction reaction (ORR) with twoelectron transference. Additionally, gold dissolution and thiosulfate degradation were evaluated using the gold foil leaching tests. It was found solutions with a 0.2 mol l -1 thiosulfate concentration favored the dissolution of gold and by maintaining an adequate ratio between thiosulfate/ammonium (1:3) or thiosulfate/copper (4:1) enable the attainment high gold dissolution and lower degradation of thiosulfate.